Adipose lipolysis is important for ethanol to induce fatty liver in the National Institute on Alcohol Abuse and Alcoholism murine model of chronic and binge ethanol feeding. Issue 5 (17th May 2023) - Mathur, Mallika; Yeh, Yu‐Te; Arya, Rakesh K.; Jiang, Long; Pornour, Majid; Chen, Weiping; Ma, Yinyan; Gao, Bin; He, Ling; Ying, Zhekang; Xue, Bingzhong; Shi, Hang; et al.
Abstract : Background and Aims: Alcohol‐associated liver disease (ALD) pathologies include steatosis, inflammation, and injury, which may progress to fibrosis, cirrhosis, and cancer. The liver receives ~60% of fatty acids from adipose tissue triglyceride hydrolysis, but the role of this lipolytic pathway in ALD development has not been directly examined in any genetic animal models with selective inactivation of adipose lipolysis. Approach and Results: Using adipose‐specific comparative gene identification‐58 (CGI‐58) knockout (FAT‐KO) mice, a model of impaired adipose lipolysis, we show that mice deficient in adipose lipolysis are almost completely protected against ethanol‐induced hepatic steatosis and lipid peroxidation when subjected to the National Institute on Alcohol Abuse and Alcoholism chronic and binge ethanol feeding model. This is unlikely due to reduced lipid synthesis because this regimen of ethanol feeding down‐regulated hepatic expression of lipogenic genes similarly in both genotypes. In the pair‐fed group, FAT‐KO relative to control mice displayed increased hepatocyte injury, neutrophil infiltration, and activation of the transcription factor signal transducer and activator of transcription 3 (STAT3) in the liver; and none of these were exacerbated by ethanol feeding. Activation of STAT3 is associated with a marked increase in hepatic leptin receptor mRNA expression and adipose inflammatory cell infiltration. Conclusions: Our findings establish a critical role of adipose lipolysis in driving hepatic steatosis and oxidative stress during ALD development. Abstract :